2007
DOI: 10.1097/fjc.0b013e31802c0cd0
|View full text |Cite
|
Sign up to set email alerts
|

In High-Risk Patients, Combination of Antiinflammatory Procedures During Cardiopulmonary Bypass Can Reduce Incidences of Inflammation and Oxidative Stress

Abstract: Previous studies showed that cardiopulmonary bypass (CPB) was directly associated with a global activation of the inflammatory response, production of oxygen free radicals, and signs of myocardial injury. We therefore evaluated, in the weakest patients, the biological and clinical benefits of a therapeutic optimization of CPB through the combination of several antiinflammatory procedures. High-risk patients undergoing cardiac surgery under CPB were included in this prospective randomized study. Control patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 26 publications
0
20
0
Order By: Relevance
“…Many studies have shown that the walls of the CPB circuit activate white cells, platelets, and the complement system. Activated leukocytes release cytotoxic agents and ROS associated with systemic inflammation and organ damage (13,14). The increase in cytokines, such as ILs and necrosis factor (4), aggravates the inflammatory response (5).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that the walls of the CPB circuit activate white cells, platelets, and the complement system. Activated leukocytes release cytotoxic agents and ROS associated with systemic inflammation and organ damage (13,14). The increase in cytokines, such as ILs and necrosis factor (4), aggravates the inflammatory response (5).…”
Section: Discussionmentioning
confidence: 99%
“…The cellular response is mediated by the main effectors of the inflammatory response, including neutrophils, which degranulate and release cytotoxic molecules such as elastase, myeloperoxidase (MPO) and free radicals[1]. Several therapeutic strategies have thus been developed to minimize this inflammation and lessen organ dysfunction[2]. In a previous study carried out in our laboratory, we measured systemic and coronary sinus free-radical release during and following removal of the cross-clamp[3].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the relatively small number of studies investigating the effects of reducing the inflammatory response to myocardial reperfusion injury, the majority of these studies has shown evidence of myocardial protection [9]. Ghrelin is an orexigenic hormone identified as an endogenous ligand for the growth hormone secretagogue receptor (GHSR) and discovery after of the growth hormone secretagogue type 1A receptor in 1996 [10] and was reported by Masayasu Kojima and colleagues in 1999 as peptide of 28 amino acids in rat and human stomachs [11].…”
Section: Introductionmentioning
confidence: 99%